Longitudinal experience-wide association studies: a framework for studying personality change - Bleidorn, Wiebke; Hopwood, Christopher J.; Back, Mitja D.; Denissen, Jaap J. A.; Hennecke, Marie; Jokela, Markus; Kandler, Christian; Lucas, Richard E.; Luhmann, Maike; Orth, Ulrich; Roberts, Brent W.; Wagner, Jenny; et al. (European journal of personality, 2020)
The importance of personality for predicting life outcomes in the domains of love, work, and health is well established, as is evidence that personality traits, while relatively stable, can change. However, little is known about the sources and processes that drive changes in personality traits and how such changes might impact important life outcomes. In this paper, we make the case that the research paradigms and methodological approaches commonly used in personality psychology need to be revised to advance our understanding of the sources and processes of personality change. We propose Longitudinal Experience-Wide Association Studies as a framework for studying personality change that can address the limitations of current methods, and we discuss strategies for overcoming some of the challenges associated with Longitudinal Experience-Wide Association Studies. © 2020 European Association of Personality Psychology
Gesehen am 26.10.2020